Analisis Faktor Risiko Stunting dan Implikasinya pada Program Gizi - Rani Suraya; Ayu Sekar Wangi; Rini Alvionita; Sultan Faqih Muhammad Lubis; Yuskaini Hadijah Rambe (Jurnal Sains Farmasi Dan Kesehatan, 2025)
The condition known as stunting, which occurs when a toddler's height is significantly below the World Health Organization's (WHO) median growth standard, is a chronic nutritional issue impacted by a number of variables, including economic circumstances, maternal nutrition, infant health, and insufficient food intake. In Indonesia, where 36.4% of people suffer from stunting, national development priorities include measures to alleviate the issue, particularly under the National Medium-Term Development Plan (RPJMN) for 2015–2019. Basic needs, education, and health are all included in the government's multi-sectoral strategy. Short-term effects of stunting include higher morbidity and growth deficiencies in children; long-term effects include changes in adult height, obesity risk, reproductive health, and productivity. One of Indonesia's Sustainable Development Goals (SDGs) is to cut stunting by 40% by 2025. At the Gunung Tinggi Community Health Centre, which runs initiatives like offering extra food and nutrition education to prevent stunting, a descriptive qualitative study was carried out. The primary initiatives include regular child development monitoring, supporting hygienic living practices, and providing food supplements to needy populations. Despite the encouraging outcomes of these programs, issues such as budget limitations, parental involvement, and population migration still exist. The program's success depends on the efforts of community health workers, or posyandu cadres, who assist families and enable the early identification of nutritional issues. In order to effectively address Indonesia's stunting epidemic, coordinated initiatives in prevention, education, and resource mobilization are necessary.